Behçet uveitis: Current practice and future perspectives - Aboul Naga, Shereen H.; Hassan, Lameece Moustafa; El Zanaty, Radwa T.; Refaat, Mohammad; Amin, Rana H.; Ragab, Gaafar; Soliman, Mahmoud M. (Frontiers in Medicine, 2022)
Described as early as Hippocrates in his “Third Book of Endemic Diseases”, Behçet’s Disease (BD), also known as “The Silk Road Disease” following its initial demographics, consists of a triad of recurrent oro-genital ulcers and associated uveitis. Current demographics and rising percentages of patients seen far beyond the Silk Road in Ocular Inflammatory Disease and Uveitis Clinics list BD uveitis as one of the frontliners of non-infectious autoinflammatory eye diseases. Clinical features of BD and juvenile-onset BD are detailed alongside various approaches in classification and suggested algorithms for diagnosis that are outlined in this review. With the ongoing Human Microbiome Project and studies such as the MAMBA study, the role of the human microbiome in BD is highlighted in the pathophysiology of BD to include the current research and literature perspective. Furthermore, with the advancement of recent diagnostic and investigative techniques, especially in the field of Optical Coherence Tomography (OCT), disease-related characteristics are updated to encompass SD, EDI and OCT-angiography characteristics of BD. Having entered the era of biologic therapy, the role of various specific cytokine-blocking biologic drugs, such as TNF-α inhibitors (e.g. adalimumab, infliximab), interferon α-2a inhibitors, IL-6 and IL-1 inhibitors are presented and contrasted alongside the conventional immunosuppressant drugs and the classic old gold standard: corticosteroids (systemic or local). Furthermore the AIDA international registry on Behçet disease is highlighted as a valuable real-life tool capable of analyzing treatment response in different clusters and geographic context. Finally, with the ongoing SARS-coV-2 pandemic, it was not possible to conclude the review without reviewing the latest evidence-based literature reporting BD morbidity in this era, the observed pattern and treatment recommendations as well as those related to reported post-vaccine complications and emergence of BD.